2014
DOI: 10.1016/j.molcel.2014.10.015
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Nuclear and Mitochondrial Genes Encoding ATP Synthase Is Synchronized by Disassembly of a Multisynthetase Complex

Abstract: In eukaryotic cells, oxidative phosphorylation involves multisubunit complexes of mixed genetic origin. Assembling these complexes requires an organelle-independent synchronizing system for the proper expression of nuclear and mitochondrial genes. Here we show that proper expression of the F1FO ATP synthase (complex V) depends on a cytosolic complex (AME) made of two aminoacyl-tRNA synthetases (cERS and cMRS) attached to an anchor protein, Arc1p. When yeast cells adapt to respiration the Snf1/4 glucose-sensing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
47
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(50 citation statements)
references
References 48 publications
3
47
0
Order By: Relevance
“…2), prompted us to ask how heat affects this complex and its activity in isolation. The complex, dubbed AME, is a heterotrimer formed by the aminoacylation cofactor Arc1 (A), methionyl-tRNA synthetase Mes1 (M), and glutamyl-tRNA synthetase Gus1 (E), which interact through eukaryote-specific N-terminal domains in each protein (Frechin et al, 2014). …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2), prompted us to ask how heat affects this complex and its activity in isolation. The complex, dubbed AME, is a heterotrimer formed by the aminoacylation cofactor Arc1 (A), methionyl-tRNA synthetase Mes1 (M), and glutamyl-tRNA synthetase Gus1 (E), which interact through eukaryote-specific N-terminal domains in each protein (Frechin et al, 2014). …”
Section: Resultsmentioning
confidence: 99%
“…The enzyme components of the AME complex, the aminoacyl-tRNA synthetases Mes1 and Gus1, have secondary transcriptional and translational activities in the nucleus and mitochondria, respectively, and are excluded from these compartments by complexing with Arc1 (Frechin et al, 2014). We hypothesize that autonomous heat-sensitive self-assembly of AME complexes discovered here confines active AME components to the cytosol, suppressing secondary activities in other compartments and focusing aminoacylation activity in the cytosol where it is needed during stress (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been shown that 4 out of 9 S. cerevisiae protein complexes that form co-translationally 49 , possibly according to a 3'UTR-complex formation model 50 , involve 6 known multifunctional and moonlighting yeast proteins 49 . Interestingly, 2 of those, MetRS and GluRS, possess nuclear and mitochondrial localization signals, which are only revealed when they proteins are not in complex with each other 51 , indicating that their co-translational complex assembly -and possibly 3'UTR-protein complex formation -may regulate their moonlighting function.…”
Section: Discussionmentioning
confidence: 99%
“…Mitochondrion is an important plant for multiple cellular biosynthesis, such as oxidative phosphorylation, tricarboxylic acid cycle, and fatty acids generation [3]. These biological processes need various enzymes or auxiliary proteins, majority of which are imported from cytosol, for ribosomes in cytosol are the places for production of various proteins or preproteins [4,5].…”
Section: Introductionmentioning
confidence: 99%